ANALYZING COMMUNICATION STRATEGIES OF PT OMRON MANUFACTURING INDONESIA IN GENDER MAINSTREAMING POLICY IMPLEMENTATION - Reni Novia; Zakiyatunnisa Abdillah (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
PT. Omron Manufacturing of Indonesia has performed a set of communication strategies to implement gender mainstreaming policies. The present study aims to analyze the implementation and constraints in the process of implementing the aforementioned policy. The present research applies a descriptive qualitative approach by conducting an in-depth analysis toward the effectiveness of communication strategies that have been used to implement gender mainstreaming policies. Furthermore, the present study uses a Miles and Huberman model to examine the communication strategies used by PT. Omron Manufacturing of Indonesia to perform gender mainstreaming policies. The results of the present study suggest the effectiveness of the intermediary and liaison between the management and employees. It can be said that the approaches taken by PT. Omron Manufacturing of Indonesia has been successful in carrying out the gender mainstreaming policies.